2022
DOI: 10.3389/fnut.2021.805612
|View full text |Cite
|
Sign up to set email alerts
|

Tea Tree Oil Terpinen-4-ol Protects Gut Barrier Integrity by Upregulation of Tight Junction Proteins via the ERK1/2-Signaling Pathway

Abstract: Tea tree oil (TTO) exhibits a potent antioxidant, antibacterial, and anti-inflammatory activity and is commonly used in skincare products. However, it is not clear whether TTO can protect gut barrier damage in inflammatory bowel disease (IBD) patients. Herein, we report the impact of terpinen-4-ol (TER, the primary constituent of TTO), on lipopolysaccharide (LPS)-induced intestinal epithelial cell barrier function impairment in intestinal porcine epithelial cell lines (IPEC-J2) and dextran sulfate sodium (DSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…In the present study, TTO significantly increased the expression of Claudin‐1 in the ileal mucosa of goats, suggesting that tea tree oil can improve the intestinal barrier and immune function. Yong et al (Yong et al, 2022 ) found that TTO could enhance intestinal barrier function by increasing the expression of Claudin‐1 in the intestines of mice, which is similar to that reported in the current study (Figure 2 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, TTO significantly increased the expression of Claudin‐1 in the ileal mucosa of goats, suggesting that tea tree oil can improve the intestinal barrier and immune function. Yong et al (Yong et al, 2022 ) found that TTO could enhance intestinal barrier function by increasing the expression of Claudin‐1 in the intestines of mice, which is similar to that reported in the current study (Figure 2 ).…”
Section: Discussionsupporting
confidence: 90%
“…Yong et al (Yong et al, 2022) found that TTO could enhance intestinal barrier function by increasing the expression of Claudin-1 in the intestines of mice, which is similar to that reported in the current study (Figure 2).…”
Section: Ta B L E 3 Effects Of Dietary Supplementation Of Tto On the ...supporting
confidence: 91%
“…Some in vitro studies have associated proanthocyanidins with augmented TEER and reduced permeability in situations of barrier dysfunction, reinforcing data obtained from GSE and GTE [ 66 , 67 ]. Also, terpinene-4-ol (primary constituent of TTO) was reported to positively impact impaired intestinal barrier function, alleviating the negative effects correlated with lipopolysaccharide (LPS) and dextran sulfate sodium (DSS) [ 68 ]. Capsicum and olive appear advantageous when applied for shorter periods, as both allowed an increase of TEER over the initial period of supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Tight junctions between epithelial cells play a role in maintaining the permeability and integrity of the intestinal mucosal barrier. Occludin and ZO-1 are the essential adhesion proteins responsible for the efficient functioning of tight junctions in the intestinal lining (Yong et al, 2021). Occludin forms a physical barrier with adjacent endothelial cells to prevent paracellular diffusion, and auxiliary proteins (ZO family) anchor the transmembrane proteins onto the cytoskeleton (Wen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%